Pneumatic Operated Engine - Sairam Jawale; Vaishnavi Dahe; Preeti Vakte; Suyog Patare; Amol Wable (International Journal of Mechanical Dynamics and Systems Analysis, 2026)
The increasing awareness of fossil fuel depletion & environmental pollution has accelerated the need for the development of sustainable & eco-friendly alternatives to traditional internal combustion engines. Pneumatically operated engines have been identified as a potential alternative for small-scale mechanical power generation owing to their advantages of zero exhaust emissions, noise reduction & operational safety. This paper describes the design, development & performance analysis of a pneumatically operated engine, which uses compressed air as a carrier energy to generate mechanical motion without combustion.The proposed system uses a double-acting pneumatic actuator controlled by a directional control valve that converts the energy of compressed air into a reciprocating piston motion. The linear motion is then converted into rotary motion using a crank-pulley and belt transmission mechanism along with a flywheel for smooth and continuous operation. The engine was designed to work at a pressure range of 3 to 6 bar & the calculations were performed to find the required piston diameter & air consumption for a force output of 2000 N.Experimental testing & graphical representation were carried out to analyze the effect of supply pressure, actuator speed & stroke time. The results show that an increase in operating pressure results in a corresponding increase in piston speed and a decrease in cycle time. At 6 bar pressure, the system performed optimally, making it suitable for driving light mechanical loads up to 200 kg. A comparative analysis with conventional internal combustion engines reveals the benefits of the new technology, which include zero emissions, reduced thermal losses, low maintenance & suitability for use in hazardous environments.Despite the limitations of the technology, including the need for a compressed air supply & lower energy density, this research work has shown that pneumatically operated engines are feasible for use in light vehicles, automation systems& and auxiliary power units. The results of this study have confirmed the potential of pneumatic engines as a sustainable alternative for specific low-power applications, thus encouraging further research in this area.
Keywords: Compressed Air Technology; Pneumatic Engine; Sustainable Engineering; green technology; zero emissions